A Blockchain-Based Emergency Message Transmission Protocol for Cooperative VANET - Ahmed, Mohiuddin; Moustafa, Nour; Akhter, A. F. M. Suaib; Razzak, Imran; Surid, Ehsanuzzaman; Anwar, Adnan; Shah, A. F. M. Shahen; Zengin, Ahmet (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2022)
The Industrial Internet of Things (IIoT) is creating a massive impact in a wide range of applications. In addition, with the forthcoming 5G and 6G technologies, vehicular ad-hoc networks will have pioneer advancements. However, security concerns are not well addressed, as vehicular networks should be deployed at a large scale. To address the security concerns, especially to ensure secure emergency message transmission, a blockchain-based protocol is proposed in this paper, where one of the blockchains is to store the authentication information of the vehicle, and another one to store and distribute blockchain services. Experimental analysis revealed that the proposed blockchain-based protocols are superior than the existing ones in terms of several metrics.
Keywords: Blockchains; Protocols; Vehicular ad hoc networks; Authentication; Servers; Security; Databases; blockchain; FDIA; IoV; PoC; VANET; MAC PROTOCOL; SCHEME; Engineering; Transportation